Utilizing local food product at rural destination - Raji, Mohd Nazri Abdul; Karim, Shahrim Ab.; Ishak, Farah Adibah Che; Arshad, Mohd Mursyid (Human Resource Management Academic Research Society, 2017)
Local food is considered as a symbol of culture destination and its people. Consuming local food is one of the memorial activities by tourists during the holiday seasons apart from fulfilling the basic needs and demands in rural destination. By participating in local food activities, it gives the opportunity to identify closely different culture and identity of a rural destination. Local food in rural destination does not only satisfy hunger, but also provides a major component of intangible heritage and becomes increasingly important attraction for tourists. Current research has found that local food at the rural destination helps to promote destination awareness, form destination identity, create tourist activity, and contribute to tourist satisfaction and experience. Thus, local food can be used as a tool to develop economies in rural destination. In tourism aspects, rural destinations tend to sell common attributes such as nature, historical sites, landscape, and cultural heritage. Integrating local food in rural destination may help to strengthen a tourist destination identity and competitiveness. Therefore, this conceptual paper provides the understanding of utilizing local food product for rural destination development domestically and globally.